Manajemen risiko likuiditas sebagai kunci stabilitas bank syariah - HIDAYATI, PUTRI NUR (Maliki Interdisciplinary Journal, 2025)
Sharia banks operate based on sharia principles that avoid usury and activities that are not in accordance with sharia. One of the main factors in maintaining the stability of sharia banks is liquidity risk management, which is the ability of banks to meet their short-term obligations on time without causing significant losses. This study uses a literature review method with a systematic approach to examine various studies related to liquidity risk management in sharia banks. The review results indicate that liquidity risk management is highly important and should be a strategic priority for Islamic banks while adhering to Sharia principles. Effective liquidity risk management can enhance operational sustainability, strengthen reputation, and maintain stability and customer trust amid market dynamics.